Tailored pore size and microporosity of covalent organic framework (COF) membranes for improved molecular separation - Shinde, Digambar B.; Cao, Li; Liu, Xiaowei; Wonanke, Dinga A.D.; Zhou, Zongyao; Hedhili, Mohamed N.; Addicoat, Matthew; Huang, Kuo-Wei; Lai, Zhiping (Journal of Membrane Science Letters, 2021)
•COF membranes with tailored pore size are designed through a de novo approach.•Ultrathin and crystalline COF membranes are prepared.•The transport mechanism through COF membrane is studied systematically. Three crystalline truxene-based β-ketoenamine COF membranes (TFP-HETTA, TFP-HBTTA and TFP-HHTTA) are fabricated via a de novo monomer design approach to understand the fundamental correlations between pore structure and molecular separation performance. By introducing bulky alkyl groups into the truxene framework, the pore size of TFP-HETTA, TFP-HBTTA, and TFP-HHTTA are systematically tuned from 1.08 to 0.72 nm. Accordingly, the TFP-HETTA showed good water permeance of 47 L m−2h−1 bar−1 along with a prominent rejection rate of Reactive Blue (RB, 800 Da) but less than 10% rejection rate of inorganic salts. In contrast, the TFP-HHTTA membrane with pore size of 0.72 nm can reject small dye molecules such as Safranin O (SO, 350 Da) and trivalent salts but with a moderate water permeance of 19 L m−2h−1 bar−1. The pore-flow model rooted from the viscous flow could well fit the observed organic solvent nanofiltration results of all three COF membranes. [Display omitted]